2021
DOI: 10.1038/s41598-021-81090-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolic remodelling patterns in Duchenne muscular dystrophy revealed by ultra-high-resolution mass spectrometry imaging

Abstract: Duchenne muscular dystrophy (DMD) is a common and severe X-linked myopathy, characterized by muscle degeneration due to altered or absent dystrophin. DMD has no effective cure, and the underlying molecular mechanisms remain incompletely understood. The aim of this study is to investigate the metabolic changes in DMD using mass spectrometry-based imaging. Nine human muscle biopsies from DMD patients and nine muscle biopsies from control individuals were subjected to untargeted MSI using matrix-assisted laser de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Elevated PC 34:1/PC 34:2 ratios were detected in DMD muscle, with higher PC 34:1/PC 34:2 ratios detected in more affected areas both in regions of regenerating fibers as well as intercellular spaces ( Tahallah et al, 2008 ). A more recent MS-imaging study also reported enhanced PC 34:1 as a prominent feature of DMD muscle ( Dabaj et al, 2021 ), however, the relationship and impact of the enhanced PC 34:1 to the membrane fragility and progressive muscle wasting remains an open and pressing question.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PC 34:1/PC 34:2 ratios were detected in DMD muscle, with higher PC 34:1/PC 34:2 ratios detected in more affected areas both in regions of regenerating fibers as well as intercellular spaces ( Tahallah et al, 2008 ). A more recent MS-imaging study also reported enhanced PC 34:1 as a prominent feature of DMD muscle ( Dabaj et al, 2021 ), however, the relationship and impact of the enhanced PC 34:1 to the membrane fragility and progressive muscle wasting remains an open and pressing question.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 ). In muscle from DMD (Duchenne muscular dystrophy) patients, increased PC and SM have been reported [ 119 ]. In EDL muscle from the mdx mice (the murine model of DMD, devoid of dystrophin), an increase PC containing saturated acyl chain (16:0 and 18:0) and a decrease PE and PC containing long and polyunsaturated acyl chain (22:6) and (20:4) were found.…”
Section: Importance Of Pls In Striated Muscle Functionsmentioning
confidence: 99%
“…A variety of muscular dystrophies are associated with a considerably perturbed skeletal muscle metabolism in both the early and acute phase of these disorder [ 318 ], including changed lipid utilisation and impaired energy metabolism in Duchenne patients [ 60 , 176 , 317 ]. Pathological developments in Duchenne children are not only characterised by highly progressive muscle wasting, but also delayed growth resulting in relatively short stature and increased fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…Besides systematic transcriptomic surveys [ 190 , 306 ] and metabolomic research [ 60 , 178 , 345 ] in the field of dystrophinopathy, a major area of omics-based biomarker discovery employs mass spectrometric and proteomic screening protocols for the large-scale identification of new peptides, protein fragments and protein biomarker candidates [ 42 , 82 ]. A few studies have also used multi-omics approaches for studying dystrophic changes at the various levels of biological organisation from gene to mRNA to protein expression [ 122 , 224 , 352 ].…”
Section: Introductionmentioning
confidence: 99%